The Aged Radio Body: Corporeality and Old Age in Beckett's All That Fall. Issue 2 (September 2020) - Querido, Pedro
Abstract : This article sets out to examine the aged radio body in Samuel Beckett's All That Fall . Its main argument is that there is a conceptual symbiosis between the radiogenic problematisation of corporeality and the deliberate thematisation of old age in All That Fall . The two main issues explored in this article – which are inextricably intertwined – concern the notion of reluctant corporeality, that is, the idea that the radiophonic body in All That Fall is very real but also frail and therefore resented; and the understanding of old age as a crucial theme that can and should be interpreted in the light of different age theories, such as disengagement theory, irremediable regret, and the réveil mortel .